La vision patrimoniale en Roumanie, entre héritage communiste et renouveau - Jérémy Vercken de Vreuschmen; Irina Iamandescu (In Situ)
1918 was a tipping point that transformed the history of Romania. It was in this year that the treaty of Bucharest was signed, declaring the birth of the nation. This young country, shortly after its creation, adopted the French model for the valorization and protection of cultural heritage. During the country’s communist and fascists regimes, The National Romanian Institute of Heritage (INP) lost influence and impact. How is national heritage considered and what is its status in Romania today? What issues and key stakeholders are involved? An interview conducted in Bucharest in 2021 with Irina Iamandescu, architect, research fellow and co-director of the INP, highlights the input from scientific research to public policies concerning the valorization of architecture, and the importance of associations as points of contact for public stakeholders. This article presents the INP’s current projects, most notably those concerning the cultural heritage of the 20th century, the reconsideration of cultural heritage in relation to climate change, the laws and regulations for the protection, valorization and accessibility of cultural heritage and the problems tied to the nation’s five decades of communist leadership.